Управління стійким організаційним розвитком великомасштабних економічних систем - Шматько, Наталія Михайлівна (Переяслав-Хмельницкий государственный педагогический университет им. Григория Сковороды, 2017)
У статі визначено необхідність вдосконалення системи управління організаційно-економічним механізмом забезпечення ефективної організації та стійкого організаційного розвитку підприємства; наведено переваги великомасштабних економічних систем перед іншими організаційними формами; розглянуто поняття "розвиток" та модель життєвого циклу великомасштабних економічних систем.

The article defines the necessity of improving the management system of the organizational and economic mechanism for ensuring an effective organization and sustainable organizational development of the enterprise; also there were presented advantages of large-scale economic systems over other organizational forms; the concept of "development" and the life cycle model of large-scale economic systems are considered.
Management of sustainable organizational development of large-scale economic systems
Keywords: економічна система; великомасштабні економічні системи; стійкий організаційний розвиток; economic system; large-scale economic systems; sustainable organizational development